Guru Penggerak and Continuous Professional Development: A Case Study of English Teachers in Palembang - Lusiana Dian Retnowati; Ismail Petrus; Rita Inderawati (AL-ISHLAH: Jurnal Pendidikan, 2024)
The study aimed to determine the significance of Guru Penggerak (GP) in developing the Continuous Professional Development (CPD) of English teachers. This was done by investigating the need for GP among English teachers to enhance their CPD and identifying the components or parts of Guru Penggerak that support their continuous professional development. A qualitative research method was used to investigate the phenomena, with two English teachers who joined Guru Penggerak Batch 1 in Palembang, South Sumatra, Indonesia as participants. Triangulation and member checks were conducted to ensure the dependability of the data obtained from interviews and documentation. The data were described and interpreted using codification, checklists, and thematic analysis. The findings of the study show that it is necessary for teachers of English to join Guru Penggerak to enhance their continuous professional development. After joining the program, English teachers were able to improve three components of their professional development: Self-Development, Scientific Publication, and Innovative Works. It was also found that GP mostly encouraged teachers of English in their pedagogical competencies, but less so in their proficiencies. However, GP provided English teachers with the eagerness to improve their English proficiency individually. Additionally, the study proved that Guru Penggerak (GP) helped advance English teachers’ careers, with some appointed as school principals and assessors of GP in subsequent Batches.